GEOCHEMICAL EFFECTS OF SMALL PACKET CRYSTALLIZATION IN LARGE MAGMA CHAMBERS–FURTHER RESOLUTION OF THE HIGHLY COMPATIBLE ELEMENT PARADOX - O'Hara M.J.; Fry N. (My University, 1996)
This is a study of the effect of solidifying a magma body by partial crystallization of a series of small packets of liquid, mixing the residual liquid into the main body of liquid before repeating the process. It confirms the major conclusions of earlier workers and demonstrates that the dominant geochemical effect of the small packet process is to sustain the relative concentrations of the compatible elements in the residual liquids from partial crystallization. Formal introduction of integrated partial crystallization ivithin the small packets of liquid enhances these effects. Incorporation of such a crystallization model into a refilled, tapped and fractionated magma body enhances the effects still more. The process affords a way to explain the anomalously high compatible element concentrations in erupted liquids which have nevertheless bun subject to substantial lowpressure crystallization. It may also have a bearing on the ratios of extremely compatible elements whose concentrations in the upper mantle are high and relatively undifferentiated relative to chondrites.